Production of volatile compounds by Geotrichum fragrans using cassava wastewater as substrate - Damasceno, S.; Cereda, M. P.; Pastore, G. M.; Oliveira, J. G. (Elsevier B.V., 2003)
The cassava processing industry generates wastewater named manipueira with a high organic content. Although considered a pollutant, manipueira can be used as substrate for fermentative processes including the cultivation of Geotrichum fragrans. This aerobic microorganism isolated from cassava wastewater has cyanide resistant respiration. Under cassava wastewater cultivation, G. fragrans produced fruit aroma volatile compounds. This study evaluated volatile compounds produced by G. fragrans in cassava liquid waste. The waste had a sugar composition composed of dextrin (2.6%), maltose (1.4%), sucrose (32.1%), glucose (38.3%), and fructose (25.6%). The average value of total sugars was 58.2 g l(-1), composed of 38.0 g l(-1) reducing and 20.2 g l(-1) non-reducing sugars. The chemical oxygen demand (COD) average value was 60 000 mg l(-1). G. fragrans used sugars (fructose and glucose) for energy generation reducing the COD value of the cassava wastewater by 40%. Biomass production of G. fragrans cultivated for 12 h in natural cassava liquid waste was 12.8 g l(-)1. The volatile compounds identified in the cassava liquid waste after 72 h cultivation were: 1-butanol, 3-methyl 1-butanol (isoamylic alcohol), 2-methyl 1-butanol, 1-3 butanodiol and phenylethanol; ethyl acetate, ethyl propionate, 2-methyl ethyl propionate and 2-methyl propanoic. The effect of substrate supplementation with glucose (50 g l(-1)), fructose (50 g l(-1)) and aqueous yeast extract (200 ml l(-1)) did not affect the qualitative and quantitative profiles of volatile compounds. These results indicate that the carbon (C) source utilized by microorganism was glucose or fructose, while nitrogen (N) supplementation was not necessary because the agent did not exhaust all the nitrogen of the wastewater. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: cassava; aroma; liquid waste; volatile compounds; Geotrichum fragrans